Análisis y mejora de los procesos y procedimientos administrativos y operativos del GADPR de Ricaurte cantón Chone - Laaz Macías, Odalis Esperanza (2023)
This research focuses on analyzing and improving administrative and operational processes and procedures in the Rural Parochial Decentralized Autonomous Government of Ricaurte, aiming to reduce time andenhancing value-added for value added to achieve these objectives, the AVA methodology (Add, Value, Save) is employed, and inspection processes are optimized. The research methodology used is descriptive, field-based, and bibliographic. Visits to the Decentralized Autonomous Government, documentary review, analysis of processes and procedures, interviews, and observations are conducted. The results obtained reveal the need to align workflow, simplify procedures, implement technological solutions, and train personnel to strengthen continuous improvement. Redundant and non-essential steps in inspection processes are identified, analyzed, and reduced using the AVA methodology. The implementation of improvement proposals enables more efficient and satisfactory service, freeing up time and resources for prioritized activities. In conclusion, it is recommended to establish clear response times, provide training to personnel, implement monitoring and evaluation systems, and promote continuous improvement to optimize processes and procedures in the Ricaurte Decentralized Autonomous Government. These actions will contribute to enhancing institutional reputation, improving customer satisfaction, and achieving greater efficiency in service delivery.